2010
DOI: 10.1093/jaoac/93.2.628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analytical Methods to Determine Sodium Content of Low-Sodium Foods

Abstract: U.S. nutrition labeling regulations require the declaration of sodium content on food products. Accurate and reproducible determination of Na in foods with low Na content (<140 mg/serving) is challenging because of laboratory contamination. Within-laboratory performance of inductively coupled plasma/MS (ICP/MS), flame atomic absorption spectrophotometry (FAAS), ion-selective electrode (ISE), and potentiometric titration of chloride ion were evaluated in 17 low-sodium foods. For 13 types of food, statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Analytical methods for the determination of salt include flame atomic absorption spectrophotometry (FAAS), inductively coupled plasma/MS (ICP/MS), ionic chromatography, and sodium selective electrodes . Other methods, such as the Volhart method (AOAC method 971.27) and potentiometric titration, measure the chloride contents, and the sodium content is then calculated stoichiometrically.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods for the determination of salt include flame atomic absorption spectrophotometry (FAAS), inductively coupled plasma/MS (ICP/MS), ionic chromatography, and sodium selective electrodes . Other methods, such as the Volhart method (AOAC method 971.27) and potentiometric titration, measure the chloride contents, and the sodium content is then calculated stoichiometrically.…”
Section: Introductionmentioning
confidence: 99%
“…The energy content was calculated based on the Atwater conversion factors (Equation ( 2)) [37]. The sodium content was evaluated according to the AOAC method 937.09 [34,38]. The cyanide contents of the uncooked and cooked CWFS and CDWFS products were analyzed as hydrogen cyanide (HCN) equivalents following the AOAC method 49.11.02 [34,35].…”
Section: Product Quality Assessmentmentioning
confidence: 99%
“…However, like the use of chloride ISE's there are many reports that the results are not reliable. Ehling et al (2010) compared the results of ICP-MS, FAAS, ISE and Cl-PT in a study that sought to identify the sodium content of a wide range of low-sodium foods. The authors found that ICP-MS was the most reproducible, in terms of consistency of results, followed by FAAS and then ISE.…”
Section: Analysis Of Sodium In Foodmentioning
confidence: 99%